James Segond correspondence - Segond, James
ALS from Segond to Gen. Edward Hand in which Segond volunteers to serve as a liaison between French and American troops during the American Revolution.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hand, Edward, -- 1744-1802 -- Correspondence; United States. -- Continental Army; United States -- History -- Revolution, 1775-1783 -- Participation, French; Army officers